ANALISIS PENERAPAN MODEL HOUSE OF RISK TERHADAP DEFECT PRODUCT PT XYZ DI PT TENARIS HYDRIL - Adinda Zaitil Chairi; Fandy Bestario Harlan (Journal of Applied Business Administration, 2022)
PT Tenaris Hydril is an Oil and Gas sector company with Pipe threading services for Accessories, Casing and Tubing types from customers with a long product process flow and each process allows defects to occur in the product. Based on PT Tenaris Hydril's Final Inspection data for the period January to December 2020, the most common defects encountered were peel off defects, to minimize defects in the product, risk management was carried out using the House of Risk (HOR) method which showed the HOR phase 1 based on ARP calculations, ranking risk and the Pareto diagram of the 80:20 principle, the results are in the form of 4 dominant risk triggers for preventive action to be taken. As well as HOR phase 2, there are 14 preventive action strategies with ratings to see which actions are taken first according to the level of ease and effectiveness.